Uma segunda língua para falar n(d)a velhice - Camargo, Teresa Cristina Ferreira (2013)
Speaking English at old age, speaking old age in English is the thread weaving this dissertation. Such sewing process started at the weekly meetings I had with those who, at old age, engaged in a kind of subversive (?) activity such as learning a second language. To respond to what they demanded (demand!) I found myself - ethically speaking - committed to undertaking a specific training: after all, I had worked with younger students, so far, At first, consistent with the involvement I had with such segment of the population, I sensed there were specificities in learning English at old age. As time passed by, the way I looked at old age has changed a great deal, what has enabled me to realize a mix of potentiality and fragility living together so as to determine the learning process at issue. That is why expressions like X is age-related I cannot accept as natural anymore. As to academic environment, I asked myself: how can I approach, theoretical-methodologically speaking, this pair of opposites - potentiality and fragility - which essentially characterizes the meeting I have had with old apprentices? Guided by these questions as well as the by need to develop them through the experience I have as an English teacher of the elderly, I met the challenge of a scientific investigation, starting my reflections on my professional practice. To start with, I supported my reflections on some Gerontology bibliography: a step ahead to go deeper into aging and old age. The result of the aforesaid endeavor can be seen in chapter 1 of this dissertation. It reflects my facing a kind of debate which is predominantly polarizing: on the one hand, propositions lying on the notion of decline; on the other hand those, more closely linked to an ideal old age, supported by the concept of active aging.Reading Mercadante (1997), Debert (1997) and Fonseca (2012), I could criticize said polarization and advocate in favor of the hypotheses that such pair of opposites, marking the human existence, should be included within Gerontological studies. Chapter 2, results from a bibliographic research as well. This time, Educational Psychology,Rosa (2010), Lajonquière (2000) and Developmental Psychology,Piaget (1985), Vygotsky (1984), - scholars - fields where the learning process is discussed - were referred to so as I could, subsequently, consider " learning English at old age" as itself. Diving into the literature concerned, Sitoe (2006), Boiavoski (2006), Silveira (2009), Morin (1999), Campos (2002), among others, I could observe some convergences, despite a few conceptual differences, that is: a) learning also means life playing a part at old age; b) recognition of the importance and suitability of the social constructivism approach to teaching English at old age. Due to the distinctness I put on Lajonquière (2000) , psychoanalyst who debates on learning as far as Education is concerned, I could understand the interaction between myself - other self is crossed by the unconscious (and, as a consequence, by desire): a third element suspending, inclusively, the notion of chronological time. The unconscious is timeless. Therefore, there is no such a link between desire and age. Therefore, desire also plays its cards in social interactions, including those motivated by learning English. The discussion submitted to the first two chapters has allowed me to position myself towards reading (analyzing) my field research data: narratives (in Portuguese and English) built by the students themselves and by me, during our meetings to learn English". Having the stamp of singularity involved in this process, I have also gathered some information which insists on being present in every student: commitment to " reinventing oneself" at old age (here meant as the demand to speak English) The methodology implemented, to meet the demand generated by such commitment, was centralize the dialog in the classroom: it is, by definition, space to opening oneself so as the other self-gains voice and talks about him/herself to one other in English. This is how, "speaking English at old age, speaking old age in English" becomes reality